Pengaruh Kedisiplinan Kerja Dan Imbalan Terhadap Peningkatan Produktivitas Kerja Karyawan Dengan Prestasi Kerja Sebagai Variabel Intervening Pada Pt Wilmar Nabati Teluk Bayur Padang - Fausta Fika; Marta Widian Sari; Ai Elis Karlinda (CV. ITTC INDONESIA, 2026)
Abstract ditulis dalam bahasa Inggris dan bahasa Indonesia (kecuali artikel yang ditulis dalam bahasa Inggris) yang This study aims to determine and analyze the influence of work discipline and rewards on employee productivity, both directly and indirectly through work performance as an intervening variable at PT Wilmar Nabati Teluk Bayur Padang. Productivity is a vital element for the sustainability of the vegetable oil processing industry amidst global competition. This research employs a quantitative method with a causal design. The population of the study comprises all 80 employees of PT Wilmar Nabati Teluk Bayur Padang. The sampling technique used is saturated sampling (census), where the entire population serves as respondents. Data collection was conducted through questionnaires using a Likert scale. Data analysis was performed using Structural Equation Modelling (SEM) based on Partial Least Square (PLS) with SmartPLS 3.0 software. The results reveal dynamic findings: (1) Work discipline has a negative and insignificant effect on work performance; (2) Rewards have a positive and significant effect on work performance; (3) Work discipline has a positive and significant direct effect on employee productivity; (4) Rewards have a negative and insignificant direct effect on employee productivity; (5) Work performance has a positive and significant effect on employee productivity; (6) Work discipline does not have a significant effect on productivity through work performance; and (7) Rewards have a significant effect on productivity through work performance. These findings indicate that to improve productivity, discipline impacts the work process directly, whereas rewards must first be converted into performance to impact productivity .